RETRACTED: Postoperative Pulmonary Complications in Patients With Transcatheter Tricuspid Valve Implantation—Implications for Physiotherapists - Yu, Peng-Ming; Wang, Yu-Qiang; Luo, Ze-Ruxing; Tsang, Raymond C. C.; Tronstad, Oystein; Shi, Jun; Guo, Ying-Qiang; Jones, Alice Y. M. (Frontiers in Cardiovascular Medicine, 2022)
Objectives To investigate the incidence of postoperative pulmonary complications (PPCs) and short-term recovery after transcatheter tricuspid valve implantation (TTVI). Methods A total of 17 patients diagnosed with severe tricuspid regurgitation who received a LuX-valve TTVI were included in this study. Spirometry lung function, maximal inspiratory pressure (MIP), and 6-min walk test distance (6MWD) were recorded. Prior to surgery, patients were stratified into high or low pulmonary risk groups based on published predefined criteria. A physiotherapist provided all patients with education on thoracic expansion exercises, effective cough and an inspiratory muscle training protocol at 50% of MIP for 3 days preoperatively. All patients received standard post-operative physiotherapy intervention including positioning, thoracic expansion exercises, secretion removal techniques and mobilization. Patients were assessed for PPCs as defined by the Melbourne-Group Score-version 2. Clinical characteristics and hospital stay, cost, functional capacity, and Kansas City Cardiomyopathy Questionnaire (KCCQ) heart failure score were recorded at admission, 1-week, and 30-days post-op. Results The mean (SD) age of the 17 patients was 68.4 (8.0) years and 15 (88%) were female. Pre-surgical assessment identified 8 patients (47%) at high risk of PPCs. A total of 9 patients (53%) developed PPCs between the 1st and 3rd day post-surgery, and 7 of these 9 patients were amongst the 8 predicted as “high risk” prior to surgery. One patient died before the 30 day follow up. Pre-operative pulmonary risk assessment score, diabetes mellitus, a low baseline MIP and 6MWD were associated with a high incidence of PPCs. Compared to those without PPCs, patients with PPCs had longer ICU and hospital stay, and higher hospitalization cost. At 30 days post-surgery, patients without PPCs maintained higher MIP and 6MWD compared to those with PPCs, but there were no significant between-group differences in other lung function parameters nor KCCQ. Conclusion This is the first study to report the incidence of PPCs post TTVI. Despite a 3-day prehabilitation protocol and standard post-operative physiotherapy, PPCs were common among patients after TTVI and significantly impacted on hospital and short-term recovery and outcomes. In the majority of patients, PPCs could be accurately predicted before surgery. A comprehensive prehabilitation program should be considered for patients prior to TTVI. Clinical Trial Registration [www.ClinicalTrials.gov], identifier [ChiCTR2000039671].